2000
DOI: 10.1046/j.1537-2995.2000.40020182.x
|View full text |Cite
|
Sign up to set email alerts
|

Apheresis‐induced platelet activation:comparison of three types of cell separators

Abstract: After 90 minutes' processing time, platelets obtained with the Amicus cell separator were significantly more activated than platelets harvested with the Spectra and the MCS+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
87
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 66 publications
15
87
1
Order By: Relevance
“…This increase appeared to be caused by the isolation of the component itself from the activation of contaminating platelets, either by the tubing or the isolation technique, because the Cobe Spectra (Gambro BCT) machines are reported to cause activation of a small amount of platelets during collection. 32 When platelet contamination is decreased by prestorage leukoreduction with a filter that removes platelets, the generation of sCD40L is decreased. These results are congruous with estimates that 95% of all human sCD40L is platelet derived, 33 both in apheresis procedures and in the collection of whole blood for separation into components.…”
Section: Discussionmentioning
confidence: 99%
“…This increase appeared to be caused by the isolation of the component itself from the activation of contaminating platelets, either by the tubing or the isolation technique, because the Cobe Spectra (Gambro BCT) machines are reported to cause activation of a small amount of platelets during collection. 32 When platelet contamination is decreased by prestorage leukoreduction with a filter that removes platelets, the generation of sCD40L is decreased. These results are congruous with estimates that 95% of all human sCD40L is platelet derived, 33 both in apheresis procedures and in the collection of whole blood for separation into components.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cardigan et al (21) reported that the reactivity of platelets to stimuli such as physiological agonists, rather than the glycoprotein expression without agonists, might be a better predictor of in vivo platelet transfusion efficacy. Recently, several studies have reported on CD62P expression in agonist-stimulated platelets for the evaluation of platelet function in platelet products (8)(9)(10)(11)(12)(13)(14)(15). However, agonist-induced expression of CD62P by flow cytometry analysis is not easy to use routinely.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, agonist-induced expression of CD62P, or other markers, has been investigated in several studies to determine platelet function in platelet products (8)(9)(10)(11)(12)(13)(14)(15), because the functional reactivity of platelets could be used to predict platelet transfusion efficacy. However, agonist-induced expression of CD62P by flow cytometry analysis has some disadvantages, including the expense of the equipment and reagents, and the difficulty of the associated procedures.…”
Section: Introductionmentioning
confidence: 99%
“…As calculated from TSD 2.5 (table 4), only TA allowed for additional units per machine per 8-hour working day compared to our current equipment. Another drawback of AM procedures consisted in higher PLT activation, also reported by Hagberg et al [38]. While PLTs harvested with MCS+, TA, TV4, or SPC were transferred intermittently or continuously to large PLT storage containers outside the centrifuge, AM PLTs were stored as 'dry PLTs' in a small bag within the centrifuge during the entire separation procedure, resulting in intimate contact with each other and the plastic material.…”
Section: Discussionmentioning
confidence: 99%